Enabling rapid parallel SERS detection with integrated microlens array - Sara Abbasi; Qing Liu; Dries Rosseel; Hugo Thienpont; Heidi Ottevaere (Sensing and Bio-Sensing Research)
Surface-enhanced Raman Spectroscopy (SERS) is a highly sensitive analytical tool with great potential for point-of-care diagnostics. However, integrating SERS with microfluidic chips poses challenges, including low signal uniformity, low light collection efficiency, and high sensitivity to optical misalignment due to the precise focusing required within microfluidic channels. This study aims to overcome these limitations by integrating a high-optical-quality Microlens Array (MLA) into a SERS-embedded platform chip. The MLA focuses light into distinct excitation points, enabling parallel Raman scattering collection and improving overall collection efficiency while reducing sensitivity to alignment issues. Integrating the MLA into the SERS platform resulted in a rise in power density from 40 W/cm2 to 700 W/cm2, leading to a fivefold improvement in the signal-to-noise (SNR) ratio of the collected Raman signal intensity. The MLA's multiplexing capability enabled the simultaneous excitation and detection of multiple analyte regions, providing high signal collection in a single run. These findings highlight the MLA-integrated SERS platform as a scalable, high-sensitivity platform for point-of-care diagnostics, real-time analysis, and high-throughput sensing, addressing critical challenges in light delivery and optical alignment demonstrated low sensitivity to misalignments in the x, y, and z axes.